1969
DOI: 10.1115/1.3571207
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamic Oscillating Compressors: Part 2—Evaluation of Specific Designs for Gas Loads

Abstract: In Part 1, electrodynamic drivers are designed for a single, linearized load. In this part, a digital computer simulation program is described. This program more accurately models the nonlinearities of the actual gas load, and can be used to check the performance of candidate designs over the expected range of loading conditions. Two selected designs, a laboratory research compressor and a commercial electrodynamic compressor, were discussed in Part 1. Simulation results for the former are discussed and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These configurations have been investigated for compressor applications and compared for power efficiency at different stroke positions [17]. Similar work has been conducted for the different linear compressor types in which the effect of the compressed gas on the piston has been expressed by an equivalent damping coefficient and a gas-spring stiffness [18][19][20][21][22]. Furthermore, Chen et al studied the static and dynamic performance of moving magnet linear compressors to identify the optimal points of the linear compressor [23].…”
Section: Introductionmentioning
confidence: 99%
“…These configurations have been investigated for compressor applications and compared for power efficiency at different stroke positions [17]. Similar work has been conducted for the different linear compressor types in which the effect of the compressed gas on the piston has been expressed by an equivalent damping coefficient and a gas-spring stiffness [18][19][20][21][22]. Furthermore, Chen et al studied the static and dynamic performance of moving magnet linear compressors to identify the optimal points of the linear compressor [23].…”
Section: Introductionmentioning
confidence: 99%
“…Both the resonant frequency and stroke are sensitive to changes in geometry and operating conditions (Cadman & Cohen, 1969;Park et al, 2004;Pollak et al, 1979;Unger & Novotny, 2002). This poses a challenge not only to compressor design but also to modeling efforts.…”
Section: Bdcmentioning
confidence: 99%
“…These two degrees of freedom are the desired piston translation and the undesired rotation of the piston within the cylinder. However, it has been observed that the resonant frequency of the linear compressor is predicted accurately using a one degree of freedom approach (Pollak et al, 1979;Cadman & Cohen, 1969). In addition, Equations (1)- (7) are linearized based on the desired input stroke.…”
Section: Resonant Frequency Of a Linear Compressormentioning
confidence: 99%